Global Perspectives on Subsidiarity
XIII, 223 p.
Keywords: Global Perspectives on Subsidiarity is the first book of its kind exclusively devoted to the principle of subsidiarity. It sheds new light on the principle and explores and develops the many applications of the principle of subsidiarity. The book provides a comprehensive overview of the principle in all its facets, from its philosophical origins in the writings of Aristotle and Aquinas, to its development in Catholic social doctrine, and its emergence as a key principle in European Union Law. This book explores the relationship between subsidiarity and concepts such as sphere sovereignty and social pluralism. It analyses subsidiarity in light of globalisation, federalism, democracy, individual rights and welfare, and discusses subsidiarity and the Australian, Brazilian and German Constitutions. .